2008
DOI: 10.1093/carcin/bgn179
|View full text |Cite
|
Sign up to set email alerts
|

Selenite reactivates silenced genes by modifying DNA methylation and histones in prostate cancer cells

Abstract: DNA hypermethylation is a common epigenetic alteration in human prostate cancer and is considered to contribute to development of this disease. Accumulating data suggest that dietary factors may alter cancer risk by modifications of epigenetic processes in the cell. The present study was designed to investigate whether selenium (Se) would alter epigenetic events to regulate methylation-silenced genes in human prostate cancer cells. DNA methylation, histone modifications and gene expression were studied in LNCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 37 publications
(54 reference statements)
2
100
0
1
Order By: Relevance
“…31 In line with reduced HDAC activity, the authors found both global and GSTP1 promoter-bound levels of H3K9ac-a repressive mark-to be increased and H3K9me3-an activating mark-to be decreased upon Se treatment. Other studies have confirmed that dietary and synthetic selenocompounds inhibit HDAC activity.…”
Section: Influence Of Se On Histone Acetylationmentioning
confidence: 88%
See 3 more Smart Citations
“…31 In line with reduced HDAC activity, the authors found both global and GSTP1 promoter-bound levels of H3K9ac-a repressive mark-to be increased and H3K9me3-an activating mark-to be decreased upon Se treatment. Other studies have confirmed that dietary and synthetic selenocompounds inhibit HDAC activity.…”
Section: Influence Of Se On Histone Acetylationmentioning
confidence: 88%
“…46 In vivo, a non-significant decrease of DNMT activity was seen in the liver and colon of rats fed Se-adequate vs. -deficient diets (0.2 and 0 mg Se/kg diet as sodium selenite). 28 Similarly, DNMT1 protein expression was diminished by 1.5 mM sodium selenite in rat cardiomyocytes 40 and in LNCaP cells 31 and by 8 mM sodium selenite and 2 mM MSA in MCF-7 cells. 47 The in vitro human and animal studies collectively indicate that Se is inversely associated with global DNA methylation and DNMT activity.…”
Section: Influence Of Selenium On Epigenetic Modifications Of Dna Andmentioning
confidence: 96%
See 2 more Smart Citations
“…Dietary selenium may also influence DNA methylation status and further influence disease predisposition, e.g. cancer [57,82,83], by affecting one-carbon metabolism in a different way compared to folate.…”
Section: Organic Chemicalsmentioning
confidence: 99%